Coming to terms with the nonmedical use of prescription medications - McCabe Sean E; Boyd Carol J (BMC, 2008)
Abstract In this commentary we highlight limitations with the way nonmedical use of prescription medications has been measured in U.S. national studies. We also offer an alternative way of conceptualizing the nonmedical use of prescription medications for future study.